11x+3=2(5x-1)+5

Simple and best practice solution for 11x+3=2(5x-1)+5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11x+3=2(5x-1)+5 equation:


Simplifying
11x + 3 = 2(5x + -1) + 5

Reorder the terms:
3 + 11x = 2(5x + -1) + 5

Reorder the terms:
3 + 11x = 2(-1 + 5x) + 5
3 + 11x = (-1 * 2 + 5x * 2) + 5
3 + 11x = (-2 + 10x) + 5

Reorder the terms:
3 + 11x = -2 + 5 + 10x

Combine like terms: -2 + 5 = 3
3 + 11x = 3 + 10x

Add '-3' to each side of the equation.
3 + -3 + 11x = 3 + -3 + 10x

Combine like terms: 3 + -3 = 0
0 + 11x = 3 + -3 + 10x
11x = 3 + -3 + 10x

Combine like terms: 3 + -3 = 0
11x = 0 + 10x
11x = 10x

Solving
11x = 10x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-10x' to each side of the equation.
11x + -10x = 10x + -10x

Combine like terms: 11x + -10x = 1x
1x = 10x + -10x

Combine like terms: 10x + -10x = 0
1x = 0

Divide each side by '1'.
x = 0

Simplifying
x = 0

See similar equations:

| 0=2x-16 | | 0.4x+4.4=3.8 | | 0=-x+15 | | o=-x+15 | | 10-2(2-x)=18 | | x+4+3+x-2+x^2+2x+3x-4=30 | | (x+7)(x+9)=2x+62 | | 20x^3-6x=0 | | (x+2)*x=80 | | 4x^2-y^2-40x-14y+15=0 | | 2x+3-4=2x-1 | | 81-3x=24x+18 | | -69-9x=9x+21 | | 122-5x=4x+15 | | 0=-2x-4 | | 6n+18=6 | | (x+2)*x=8 | | (D^3+4D^2-3D-18)y=0 | | 0.4x+4.5=0.3x+2.5 | | 6a-6+4a=4a+24 | | p+6.5p=27 | | -12=6x-8x-22 | | 7(3-0.5k)=3k-5 | | .625y-7=3 | | 5(5-12)-24=3(s+2) | | -2x-y=10 | | -5.6x=-19.04 | | x(3x-1)=x^2+15 | | 6x-15y=60 | | 7x+3=5x+12 | | 3x^2-x^2-x=15 | | t-2(3w-2t)=2t+9 |

Equations solver categories